Systematic Review and Critique of the Contributions of Traditional Ecological Knowledge of Beluga Whales in the Marine Mammal Literature + Supplementary Appendix Table (See Article Tools) - Breton-Honeyman, Kaitlin; Furgal, Chris M.; Hammill, Michael O. (ARCTIC, 2016)
In this study we systematically review and critique literature containing Traditional Ecological Knowledge (TEK) of the beluga (Delphinapterus leucas) as a case study to gain insights into TEK’s contributions to the marine mammal literature over the past four decades. We reviewed multiple searchable online databases, collected both academic and grey literature, and categorized it by geographic and disciplinary focus, as well as by the contribution of TEK to the source. Of the total 137 papers retained in the final analysis, 67% referred to the Canadian North, particularly the Hudson Bay subregion. Articles that included informal or anecdotal representations of TEK of belugas were the most prevalent. The number of papers containing TEK of belugas increased rapidly between 1975 and 2004 but appears to have leveled off since then. Biological papers represented the largest disciplinary focus (72%), followed by papers on management or co-management. This review showed that although knowledge of Indigenous peoples has made substantial contributions to the understanding of beluga, there is a lack of explicit collection, documentation, and use of TEK in the literature on belugas and particularly in the literature on beluga management. Dans cette étude, nous avons passé en revue de manière systématique la littérature existante sur les connaissances écologiques traditionnelles (CÉT) des bélugas (Delphinapterus leucas) et nous l’avons critiquée en tant qu’étude de cas dans le but de mieux comprendre la contribution des CÉT aux connaissances existantes sur les mammifères marins au cours des quatre dernières décennies. Différentes bases de données consultables en ligne ont été examinées, puis des articles publiés dans des revues scientifiques et des écrits provenant de la littérature grise ont été recueillis, après quoi ceux-ci ont été classés par emplacement géographique, discipline, ainsi que par leur utilisation des CÉT. Au total, 137 documents ont été retenus pour les analyses finales, dont 67 % faisaient référence au ...